وسائل الدفع الإلكتروني في الجزائر-الواقع والتحديات - شملول، حسينة (University of Eloued جامعة الوادي, 2025)
تناولت هذه الدراسة واقع وسائل الدفع الإلكتروني في الجزائر، بالتركيز على تحليل الوضع الحالي والإجراءات المتخذة في سبيل ترقيتها وتوسيع استخدامها، إلى جانب التعرف على أبرز التحديات التي تعترض طريق تطوير هذا القطاع الحيوي، واقتراح حلول عملية لتعزيز فاعليته ودوره في دعم التحول الرقمي والتنمية الاقتصادية. وتوصلت الدراسة إلى أن تطبيق وسائل الدفع الإلكتروني في الجزائر ما زال يواجه بعض الصعوبات والتحديات رغم الجهود المبذولة من طرف السلطات العمومية والقطاع المصرفي من أجل رقمنة المعاملات وتطوير البنية التحتية المالية، وأن الدفع نحو اقتصاد غير نقدي يتطلب رؤية شاملة، ترتكز على تطوير البنية التحتية الرقمية، تعزيز الثقافة المالية، وتفعيل الأطر القانونية والتنظيمية التي تواكب التطور لتتمكن وسائل الدفع الحديثة أن تࣳسهم في تحقيق التنمية المستدامة في الجزائر. This study addresses the reality of electronic payment methods in Algeria, focusing on analyzing the current situation, and the measures taken to promote their usage. It also identifies the main challenges hindering the development of this vital sector and proposes practical solutions to enhance its role in supporting digital transformation and economic development. The study concludes that, despite the efforts made by public authorities and the banking sector, the implementation of electronic payment methods in Algeria still faces several difficulties. The shift towards a cashless economy requires the development of digital infrastructure and the activation of legal and regulatory frameworks that keep modern payment methods to contribute to achieving sustainable development in Algeria.
“Electronic Payment Methods – Reality and Challenges"
مقال
Keywords: وسائل الدفع الإلكتروني; البطاقة البنكية; البطاقة البريدية الذهبية; الرقمنة; Electronic payment methods; bankcard; Edahabia card; digitization.